Milling of Technical Ceramics ROCAR SiSiC - Stancekova, Dana; Mrázik, Jozef; Görögová, Ingrid; Miturska, Izabela; Ščotka, Peter; Turian, Filip (Manufacturing Technology Journal, 2020)
The paper deals with hard machining of ceramic construction materials that are still more applied in the automo-bile industry as well as other branches due to their specific properties, such as hardness, corrosion resistance, heat resistance, etc. Concretely, we speak of milling of technical ceramics ROCAR SiSiC. Our intention is the right se-lection of suitable tool materials, tool geometry as well as a definition of optimum cutting parameters by the min-imum cost. After the selection of optimum technology, identified cutting plates were compared and experimentally verified in the process. Results of verifications the right choice of selected cutting plate is a comparison of compo-nents of cutting force originating in the process of machining and also the quality of machined surfaces after mill-ing of hard and brittle material.
Keywords: Milling; Technical ceramics; Cutting forces; Surface quality